Are swimming coaches ready to help injured young swimmers? - Dimitrić Goran; Jakšić Milorad; Sadri Filip; Zenić Nataša (Sciendo, 2022)
Study aim: This study aimed to determine the knowledge and skills of swimming coaches in providing first aid and cardiopulmonary resuscitation (CPR).